Survey of Aspergillus section Flavi presence in agricultural soils and effect of glyphosate on nontoxigenic A. flavus growth on soil-based medium - Carranza, Cecilia Soledad (2014)
Aims To evaluate the cultivable mycobiota from agricultural soils exposed to pesticides, the aflatoxigenic capacity of Aspergillus section Flavi strains and the effect of glyphosate on lag phase and growth rates of native nontoxigenic Aspergillus flavus under different water potential (MPa) conditions on soil-based medium. Methods and Results Culturable mycobiota analysis from different agricultural soils was performed by the surface spread method. The effect of glyphosate (0–20 mmol l−1) on the growth of A. flavus strains was evaluated on a soil extract solid medium. Mycobiota analysis of crop soils showed the presence of twenty-one genera of filamentous fungi. Aspergillus flavus and Aspergillus niger aggregate strains were isolated from the three soil types. Ninety-two per cent of A. flavus strains were toxigenic. In vitro assay results showed that at −0·70 MPa, a significant increase in growth rate in all strains was recorded at 5 and 20 mmol l−1 of glyphosate. At −2·78 MPa, this parameter remained constant at all glyphosate concentrations, except in GM4 strain where an increase in growth rate was recorded with increasing pesticide concentrations. At −7·06 MPa, a significant increase in growth rate has also been observed in GM 3 strain with 5 mmol l−1 and in GM 4 strain with 10 and 20 mmol l−1. Conclusions This study showed that the imperfecti fungi Aspergillus spp., Penicillium spp., Trichoderma spp., Cladosporium spp. and Paecilomyces spp. are isolated as prevalent groups in agricultural soil exposed to pesticides, and the capacity of nontoxigenic A. flavus strains to tolerate different glyphosate concentrations under different water potential (MPa) conditions. Significance and Impact of the Study This manuscript makes a contribution to the knowledge of cultivable fungal populations from agricultural soils exposed to pesticides and the glyphosate tolerance of A. flavus strains.